Three-month functional outcomes following endovascular thrombectomy during the first wave of the COVID-19 pandemic: a Canadian single-center cohort study. (2nd June 2021) - Neves Briard, Joel; Dufort, Gabrielle; Jacquin, Grégory; Alesefir, Walid; Bereznyakova, Olena; Boisseau, William; Daneault, Nicole; Deschaintre, Yan; Diestro, Jose Danilo Bengzon; Ducroux, Célina; Eneling, Johanna; Gioia, Laura; et al.
Abstract : Background: The COVID-19 pandemic has disrupted acute stroke care logistics, including delays in hyperacute management and decreased monitoring following endovascular therapy (EVT). We aimed to assess the impact of the pandemic on 90-day functional outcome among patients treated with EVT. Methods: This is an observational cohort study including all patients evaluated for an acute stroke between March 30, 2020 and September 30, 2020 (pandemic cohort) and 2019 (reference cohort) in a high-volume Canadian academic stroke center. We collected baseline characteristics, acute reperfusion treatment and management metrics. For EVT-treated patients, we assessed the modified Rankin score (mRS) at 90 days. We evaluated the impact of the pandemic on a 90-day favourable functional status (defined as mRS 0–2) and death using multivariable logistic regressions. Results: Among 383 and 339 patients included in the pandemic and reference cohorts, baseline characteristics were similar. Delays from symptom onset to evaluation and in-house treatment were longer during the early first wave, but returned to reference values in the subsequent months. Among the 127 and 136 EVT-treated patients in each respective cohort, favourable 90-day outcome occurred in 53/99 (53%) vs 52/109 (48%, p=0.40), whereas 22/99 (22%) and 28/109 (26%, p=0.56) patients died. In multivariable regressions, the pandemic period was not associated with 90-day favourable functional status (aOR 1.27, 95% CI 0.60 to 2.56) or death (aOR 0.74, 95% CI 0.33 to 1.63). Conclusion: In this single-center cohort study conducted in a Canadian pandemic epicenter, the first 6 months of the COVID-19 pandemic did not impact 90-day functional outcomes or death among EVT-treated patients.